SURVEILLANCE AS THE BASIS OF MODERN SCIENTIFIC AND METHODICAL APPROACH TO THE ANALYSIS OF THE EPIDEMIOLOGICAL SITUATION OF TUBERCULOSIS - L. P. Aksyutina (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
On the territory in Omsk region for 20 years has been an active epidemiological surveillance of tuberculosis infection. The author presents data of epidemiological surveillance of tuberculosis infection in the region.